# Cauchy's Convergence Criterion/Real Numbers/Sufficient Condition/Proof 3

## Theorem

Let $\sequence {x_n}$ be a sequence in $\R$.

Let $\sequence {x_n}$ be a Cauchy sequence.

Then $\sequence {x_n}$ is convergent.

## Proof

The aim is to define two sequences whose elements are respectively upper and lower bounds to subsequences of the sequence $\sequence {a_n}$.

It is then shown that these two sequences converge to the same limit.

This is used to prove that $\sequence {a_n}$ converges.

A sequence $\sequence {\epsilon_i}$ is introduced that can be considered a sequence of values or levels that a positive, real variable $\epsilon$ ($ \ge 1$) passes through on its way towards $0$.

At each level an upper bound and a lower bound for a subsequence of $\sequence {a_n}$ are defined.

All such upper bounds form a sequence of upper bounds and the lower bounds a sequence of lower bounds.

These two sequences are the ones that are used to show that $\sequence {a_n}$ converges.

Let $\sequence {a_n}$ be a Cauchy sequence in $\R$.

Since $\sequence {a_n}$ is Cauchy, for every $\epsilon \in \R_{>0}$ a natural number $N$ exists such that:

- $\size {a_n - a_m} < \epsilon$ for every $m, n \ge N$

We aim to show that $\sequence {a_n}$ converges.

That is, that a real number $a$ exists and for every $\epsilon \in \R_{>0}$ a natural number $N'$ exists such that:

- $\size {a_n - a} < \epsilon$ for every $n > N'$

Let $\sequence {\epsilon_i}_{i \mathop \in \N}$ be a sequence of strictly positive real numbers that satisfies:

- $\epsilon_0 = 1$
- $\epsilon_{i + 1} < \epsilon_i$ for every $i \in \N$
- $\ds \lim_{i \mathop \to \infty} \epsilon_i = 0$

### $a_n$ is between and arbitrarily close to elements of two sequences

Since $\sequence {a_n}$ is Cauchy, for each $\epsilon_i$ a natural number $N_i$ exists such that:

- $\size {a_n - a_m} < \epsilon_i$ for every $m, n \ge N_i$

Therefore, we have for every $i \in \N$:

\(\ds \size {a_n - a_m}\) | \(<\) | \(\ds \epsilon_i\) | for every $m, n \ge N_i$ | |||||||||||

\(\ds \leadsto \ \ \) | \(\ds \size {a_n - a_{N_i} }\) | \(<\) | \(\ds \epsilon_i\) | for every $n \ge N_i$ | ||||||||||

\(\ds \leadsto \ \ \) | \(\ds a_{N_i} - \epsilon_i\) | \(<\) | \(\ds a_n < a_{N_i} + \epsilon_i\) | for every $n \ge N_i$ by Negative of Absolute Value: Corollary 1 |

Let us study the sequence $\sequence {N_i}_{i \mathop \in \N}$.

Consider the relation between $N_{i + 1}$ and $N_i$.

We have, for every $i \in \N$:

- $\size {a_n - a_m} < \epsilon_i$ for every $m, n \ge N_i$

and:

- $\size {a_n - a_m} < \epsilon_{i + 1}$ for every $m, n \ge N_{i + 1}$

We have that $\epsilon_{i + 1} < \epsilon_i$ for every $i \in \N$.

Accordingly, $N_{i + 1}$ should be at least as great as $N_i$.

Therefore, we choose the value of $N_{i + 1}$ so that:

- $N_{i + 1} \ge N_i$ for every $i \in \N$

$\Box$

Define a real sequence $\sequence {u_i}_{i \mathop \in \N}$ by:

- $u_0 = a_{N_0} + \epsilon_0$
- $u_{i + 1} = \min \set {u_i, a_{N_{i + 1} } + \epsilon_{i + 1} }$ for every $i \in \N$

We observe that $u_{i + 1}$ is the minimum of two numbers, one of which is $u_i$.

Therefore $\sequence {u_i}$ is decreasing.

### $u_i$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$

We prove this by using the Principle of Mathematical Induction.

We have that $a_n < a_{N_0} + \epsilon_0$ whenever $n \ge N_0$.

Therefore, $a_{N_0} + \epsilon_0$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_0}$.

Furthermore, $u_0$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_0}$ since $u_0 = a_{N_0} + \epsilon_0$.

This concludes the first induction step.

We need to prove that $u_{i + 1}$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_{i + 1} }$ if $u_i$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$.

Assume that $u_i$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$.

$u_{i + 1}$ equals either $u_i$ or $a_{N_{i + 1} } + \epsilon_{i + 1}$.

First, assume that $u_{i + 1} = u_i$.

We have that $u_i$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$ by presupposition.

Therefore, $u_{i + 1}$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$ as $u_{i + 1} = u_i$.

We have that $\sequence {a_n}_{n \mathop \ge N_{i + 1} }$ is a subsequence of $\sequence {a_n}_{n \mathop \ge N_i}$ because $N_{i + 1} \ge N_i$.

Therefore, an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$ is also an upper bound for $\sequence {a_n}_{n \mathop \ge N_{i + 1} }$.

Therefore, $u_{i + 1}$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_{i + 1} }$ because $u_{i + 1}$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$.

This concludes the first part of the second induction step.

Now, assume that $u_{i + 1} = a_{N_{i + 1} } + \epsilon_{i + 1}$.

We have that $a_n < a_{N_{i + 1} } + \epsilon_{i + 1}$ whenever $n \ge N_{i + 1}$.

In other words, $a_{N_{i + 1} } + \epsilon_{i + 1}$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_{i + 1} }$.

Therefore, $u_{i + 1}$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_{i + 1} }$ as $u_{i + 1} = a_{N_{i + 1} } + \epsilon_{i + 1}$.

This concludes the proof that $u_i$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$ for every $i \in \N$.

$\Box$

### $\sequence {u_i}$ converges

$\sequence {a_n}$ is bounded by Real Cauchy Sequence is Bounded.

Therefore, $\sequence {a_n}$ has a lower bound $b$.

$\sequence {a_n}_{n \mathop \ge N_i}$ is a subsequence of $\sequence {a_n}$ for every $i \in \N$.

Therefore, $b$ is also a lower bound for $\sequence {a_n}_{n \mathop \ge N_i}$.

We have that $u_i$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$.

Therefore, $b$ is less than or equal to $u_i$ for every $i$.

So, $\sequence {u_i}$ is bounded below.

Since $\sequence {u_i}$ is decreasing, its first element is an upper bound for $\sequence {u_i}$.

Since $\sequence {u_i}$ is bounded below and above, it is bounded.

We have that$ \sequence {u_i}$ is bounded and decreasing.

Therefore $\sequence {u_i}$ converges by the Monotone Convergence Theorem.

$\Box$

Now, define a real sequence $\sequence {l_i}_{i \mathop \in \N}$ by:

- $l_0 = a_{N_0} - \epsilon_0$
- $l_{i + 1} = \max \set {l_i, a_{N_{i + 1} } - \epsilon_{i + 1} }$ for every $i \in \N$

### $l_i$ is a lower bound for $\sequence {a_n}_{n \mathop \ge N_i}$, and $\sequence {l_i}$ converges

An analysis of $\sequence {l_i}$ is similar to the one above of $\sequence {u_i}$.

Therefore, it is not given here.

It produces the following results:

- $\sequence {l_i}$ is increasing

- $l_i$ is a lower bound for $\sequence {a_n}_{n \mathop \ge N_i}$ for every $i \in \N$

- $\sequence {l_i}$ converges

$\Box$

### The limits of $\sequence {u_i} $ and $\sequence {l_i}$ as $i \to \infty$ are equal

We have that $u_i$ and $l_i$ are, respectively, upper and lower bounds for $\sequence {a_n}_{n \mathop \ge N_i}$ for every $i \in \N$.

This means that, for every $n \ge N_i$ for every $i \in \N$:

\(\ds l_i\) | \(\le\) | \(\ds a_n \le u_i\) | ||||||||||||

\(\ds \leadsto \ \ \) | \(\ds l_i\) | \(\le\) | \(\ds u_i\) | |||||||||||

\(\ds \leadsto \ \ \) | \(\ds 0\) | \(\le\) | \(\ds u_i - l_i\) |

Therefore, we have for every $i \in \N$:

\(\ds 0\) | \(\le\) | \(\ds u_{i + 1} - l_{i + 1}\) | ||||||||||||

\(\ds \) | \(=\) | \(\ds \min \set {u_i, a_{N_{i + 1} } + \epsilon_{i + 1} } - \max \set {l_i, a_{N_{i + 1} } - \epsilon_{i + 1} }\) | Definitions of $u_{i + 1}$ and $l_{i + 1}$ | |||||||||||

\(\ds \) | \(\le\) | \(\ds a_{N_{i + 1} } + \epsilon_{i + 1} - \max \set {l_i, a_{N_{i + 1} } - \epsilon_{i + 1} }\) | because $\min \set {u_i, a_{N_{i + 1} } + \epsilon_{i + 1} } \le a_{N_{i + 1} } + \epsilon_{i + 1}$ | |||||||||||

\(\ds \) | \(\le\) | \(\ds a_{N_{i + 1} } + \epsilon_{i + 1} - \paren {a_{N_{i + 1} } - \epsilon_{i + 1} }\) | because $\max \set {l_i, a_{N_{i + 1} } - \epsilon_{i + 1} } \ge a_{N_{i + 1} } - \epsilon_{i + 1}$ | |||||||||||

\(\ds \) | \(=\) | \(\ds 2 \epsilon_{i + 1}\) |

This shows that $u_i - l_i \to 0$ as $i \to \infty$ since $\ds \lim_{i \mathop \to \infty} \epsilon_i = 0$.

We have:

\(\ds \lim_{i \mathop \to \infty} u_i - \lim_{i \mathop \to \infty} l_i\) | \(=\) | \(\ds \lim_{i \mathop \to \infty} (u_i - l_i)\) | Combined Sum Rule for Real Sequences as $\sequence {u_i}$ and $\sequence {l_i}$ converge | |||||||||||

\(\ds \leadstoandfrom \ \ \) | \(\ds \lim_{i \mathop \to \infty} u_i - \lim_{i \mathop \to \infty} l_i\) | \(=\) | \(\ds 0\) | as $\ds \lim_{i \mathop \to \infty} (u_i - l_i) = 0$ | ||||||||||

\(\ds \leadstoandfrom \ \ \) | \(\ds \lim_{i \mathop \to \infty} u_i\) | \(=\) | \(\ds \lim_{i \mathop \to \infty} l_i\) |

$\Box$

### $\sequence {a_n}$ converges

Let $\ds a = \lim_{i \mathop \to \infty} u_i = \lim_{i \mathop \to \infty} l_i$.

We have for every $i \in \N$:

\(\ds l_i\) | \(\le\) | \(\ds a \le u_i\) | as $\sequence {l_i}$ is increasing and $\sequence {u_i}$ is decreasing | |||||||||||

\(\ds \leadstoandfrom \ \ \) | \(\ds 0\) | \(\le\) | \(\ds a - l_i \le u_i - l_i\) | |||||||||||

\(\ds \leadsto \ \ \) | \(\ds \size {a - l_i}\) | \(\le\) | \(\ds \size {u_i - l_i}\) |

Also, we have for every $n \ge N_i$ for every $i \in \N$:

\(\ds l_i\) | \(\le\) | \(\ds a_n \le u_i\) | as $l_i$ is a lower bound for $\sequence {a_n}_{n \ge N_i}$ and $u_i$ is an upper bound for $\sequence {a_n}_{n \mathop \ge N_i}$ | |||||||||||

\(\ds \leadstoandfrom \ \ \) | \(\ds 0\) | \(\le\) | \(\ds a_n - l_i \le u_i - l_i\) | |||||||||||

\(\ds \leadsto \ \ \) | \(\ds \size {a_n - l_i}\) | \(\le\) | \(\ds \size {u_i - l_i}\) |

Let $\epsilon \in \R_{>0}$.

A natural number $j$ exists such that, for every $i \ge j$:

\(\ds \size {u_i - l_i}\) | \(<\) | \(\ds \dfrac \epsilon 2\) | as $\ds \lim_{k \mathop \to \infty} (u_k - l_k) = 0$ |

Putting all this together, we find for every $n \ge N_j$:

\(\ds \size {a_n - a}\) | \(=\) | \(\ds \size {a_n - l_j + l_j - a}\) | ||||||||||||

\(\ds \) | \(\le\) | \(\ds \size {a_n - l_j} + \size {l_j - a}\) | Triangle Inequality for Real Numbers | |||||||||||

\(\ds \) | \(\le\) | \(\ds \size {u_j - l_j} + \size {l_j - a}\) | as $\size {a_n - l_j} \le \size {u_j - l_j}$ | |||||||||||

\(\ds \) | \(\le\) | \(\ds \size {u_j - l_j} + \size {u_j - l_j}\) | as $\size {a - l_j} \le \size {u_j - l_j}$ | |||||||||||

\(\ds \) | \(=\) | \(\ds 2 \size {u_j - l_j}\) | ||||||||||||

\(\ds \) | \(<\) | \(\ds \epsilon\) | as $\ds \size {u_j - l_j} < \frac \epsilon 2$ |

This finishes the proof that $\sequence {a_n}$ is convergent.

$\blacksquare$